Periodontal Inflamed Surface Area Mediates the Link between Homocysteine and Blood Pressure - João Botelho; Vanessa Machado; Yago Leira; Luís Proença; José João Mendes (Biomolecules, 2021)
Here, we assess the association between homocysteine (Hcy) serum levels and periodontal status in a large representative sample of the National Health and Nutrition Examination Survey (NHANES). Using the 2001–2002 and 2003–2004 NHANES databases, participants with a periodontal examination, medical self-reported data, blood pressure (BP) and blood samples to determine complete blood count, C-reactive protein (CRP) and Hcy levels. We then calculated the periodontal inflamed surface area (PISA) and the periodontal epithelial surface area (PESA). Multivariable regression analysis explored the association between Hcy, periodontal measures and BP. Mediation analysis was performed to understand the effect of PISA and PESA in the link between Hcy and BP. 4021 participants fulfilled the inclusion criteria. Hcy levels showed significant correlations with systolic BP, diastolic BP, PISA, PESA and age. PESA showed to be significantly associated with Hcy both for the crude and adjusted models (p < 0.01), but not PISA (p > 0.05). In the association of Hcy with systolic BP, PISA significantly mediated 17.4% and PESA 0.9%. In the association of Hcy with diastolic BP, PISA significantly mediated 16.3% and PESA 47.2%. In conclusion, Hcy and periodontitis are associated. Further, both PISA and PESA significantly mediated the association of Hcy with systolic BP and diastolic BP. Future studies shall deepen the mechanisms by which Hcy levels increase in a clinical situation of periodontitis.